PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN KONSUMEN TERHADAP KOTAK MISTERI (MYSTERY BOX) - Muhammad Rifqi Eka Nurfitrah; Asram A.T Jadda; Wahyu Rasyid; Hartono Hamzah; Nurhaedah Hasan (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study aims to determine the concept of Mystery Box buying and sellingactivities in E-Commerce and to determine the validity of Mystery Box buying andselling activities online in E-Commerce according to the Consumer ProtectionLaw, using qualitative descriptive data analysis. The findings obtained from thisstudy include: (1) The legal perspective on the concept of Mystery Box buyingand selling in E-Commerce is that the buying and selling activities of mysteryboxes are in accordance with the applicable regulations in Indonesia, namelyArticle 1320 of the Civil Code, Law of the Republic of Indonesia Number 8 of1999 concerning Consumer Protection, Article 46 paragraph (2) of GovernmentRegulation Number 71 of 2019 concerning the Implementation of ElectronicSystems and Transactions, and Islamic Law. (2) The legality of online MysteryBox buying and selling activities in E-Commerce applications based on theConsumer Protection Act and several other applicable supporting regulations isinvalid, far from fair or ideal, because there are still many sellers who violateapplicable legal regulations.